2021
DOI: 10.1088/1555-6611/abd8cb
|View full text |Cite
|
Sign up to set email alerts
|

Optical bistability in reflection of the laser pulse in a 1D photonic crystal doped with four-level InGaN/GaN quantum dots

Abstract: The present study aimed to evaluate the optical properties of 1D photonic crystal (PC) with a defect layer doped by four-level InGaN/GaN quantum dots. Transient and steady-state behavior of the medium completely relies on the intensities and relative phases of coherent coupling fields. In addition, the transient absorption–dispersion spectra of 1DPC can be easily adjusted by choosing the controllable parameters properly. Furthermore, the transmitted and reflected light pulses at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…. (25) To distinguish between the real and imaginary components of r(ω) and t(ω), we express them in the form t(ω) = |t(ω)| exp[iϕ t (ω)] and r(ω) = |r(ω)| exp[iϕ r (ω)] respectively, where the real functions ϕ t,r (ω) correspond to the phases of the transmission and reflection coefficients. The phase times for transmitted and reflected pulses can be computed using the relation τ r,t (ω) = ∂ϕ r,t / ∂ω [33].…”
Section: Pulse Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…. (25) To distinguish between the real and imaginary components of r(ω) and t(ω), we express them in the form t(ω) = |t(ω)| exp[iϕ t (ω)] and r(ω) = |r(ω)| exp[iϕ r (ω)] respectively, where the real functions ϕ t,r (ω) correspond to the phases of the transmission and reflection coefficients. The phase times for transmitted and reflected pulses can be computed using the relation τ r,t (ω) = ∂ϕ r,t / ∂ω [33].…”
Section: Pulse Propagationmentioning
confidence: 99%
“…They found that by adjusting the optical parameters of the system, the reflection and transmission lights can be tuned in different thickness of the defect layer. Controlling the optical bistability and optical multistability in a defect 1DPC doped by four-level quantum dot have been studied by Shiri et al [25]. They discussed the intensity of the coupling light on the optical bistability threshold of the reflected light.…”
Section: Introductionmentioning
confidence: 99%
“…spontaneously generated coherence (SGC) [7], high refractive index [8], and many more surprising effects [9][10][11][12][13][14][15][16][17]. Because of this, EIT has been examined in a variety of different architectures, including multilevel atoms and semiconductor quantum well (QW) nanostructures, respectively [18][19][20][21]. The opacity number one system will turn transparent via quantum interference due to coherent states in a standard three-level EIT system because of the use of a strong coherent pair field.…”
Section: Introductionmentioning
confidence: 99%
“…This endeavor presently stands as the ultimate objective of most telecommunication research [7,[11][12][13]. In recent times, quantum wells or coupled-quantum wells and coupled-quantum dots (CQDs) have predominantly been employed for the development of all-optical systems [14][15][16][17]. These materials possess properties similar to atomic vapors, such as discrete energy levels, and offer advantages such as large electric dipole moments and high nonlinear optical coefficients.…”
Section: Introductionmentioning
confidence: 99%